Anesthetic Management of Emergency Cesarean Delivery in a Patient With Noonan and Eisenmenger Syndromes: Case Report. Issue 2 (March 1994) - Lawlor, Michael C.; Johnson, Calvin
Abstract : Background and Objectives: A parturient with both Eisenmenger and Noonan syndromes presented for emergency cesarean delivery. Methods: The anesthetic technique included spinal anesthesia with bupivacaine and fentanyl, oxygen, and rapid correction of hypotension with phenylephrine. Special circumstances precluded the use of invasive monitoring. Intraoperative monitoring consisted of ECG, pulse oximetry, and noninvasive blood pressure. A continuous epidural infusion of fentanyl was utilized for postoperative pain management. Results: A cesarean delivery was successfully performed and both mother and infant were eventually discharged from the hospital. Conclusion: This case report emphasizes the issues of importance to anesthesiologists in regard to Eisenmenger and Noonan syndromes and describes a successful technique for caring for a complex patient in an emergency situation.